Vanha mies - Matikainen, Antti, 1979-; Vuorenmaa, Antti, 1970-; Vuorenmaa, Antti, 1970-; Hilland Records ([Kustannuspaikka tuntematon] : Hilland Records, 2009)
1 kappale.
Antti Matikainen (lauluääni), yhtye.
Keywords: Matikainen, Antti, -- 1979- -- singlet; viihdemusiikki